Structural and chemical characterization of Ti-ZrO2-PO4-3 protective coatings for biomedical applications - Severo, Vinícius A.; Pinheiro, Lailla Daianna Soltau Missio; Volkmer, Tiago Moreno; Raffin, Renata Plactcheck; Fagan, Solange Binotto; Bulhões, Luis Otavio de Sousa (Disciplinarum Scientia | Naturais e Tecnológicas, 2017)
The development of new materials have provided great advances in biomedical implant properties. Despite these, some problems such as chemical stability and osseointegration still have evident negative effects in many patients. To improve the properties of these materials, the main goal of this work is to develop zirconium oxide (ZrO2) coatings containing phosphate, by sol-gel process, deposited on titanium (Ti) substrate. The precursor solution was prepared by the dissolution of zirconium acetylacetonate in a mixture of acetone, ethylene glycol, ethanol, water and phosphoric acid. The substrate has been coated with gel containing the precursor material, by a dip-coating process. For samples characterization, a crystal structure of the films by X-ray diffraction (XRD), chemical stability by voltammetry and potential balance were evaluated. The diffraction analysis of x-rays showed that it was possible to coat the titanium with zirconium pyrophosphate in the sol-gel process. An increase on corrosion resistance was observed on the titanium surface containing the film.